In silico design of a multi-epitope rabies vaccine candidate incorporating African HLA diversity: A reverse vaccinology approach - Moh R. Afnani; Nur F. Emilia; Efi Nurlaili; Anwar Rovik; Arif NM. Ansori; Arli A. Parikesit; Shrabonti Chatterjee; Joydeep Mahata; Athika Firdous; Sukma Sahadewa; Aswin R. Khairullah; I MDM. Adnyana; Maksim Rebezov; Abdugani Abdurasulov; Fara D. Durry; Rollando Rollando (Narra Sains Indonesia, 2026)
Rabies remains a neglected zoonotic disease with disproportionately high incidence and mortality across African regions, highlighting the need for improved and population-tailored preventive strategies. The aim of this study was to design and evaluate a multi-epitope rabies vaccine candidate targeting the rabies virus glycoprotein using a reverse vaccinology and immunoinformatics approach, with consideration of African human leukocyte antigen (HLA) allele diversity. A total of eleven cytotoxic T-lymphocyte (CTL), nine helper T-lymphocyte (HTL), and nine B-cell linear epitopes were predicted and subsequently filtered based on immunogenicity, interferon-gamma (IFN-γ) induction potential, antigenicity, allergenicity, and toxicity. The selected epitopes were assembled into a vaccine construct using appropriate adjuvants and immunostimulatory linkers. Population coverage analysis demonstrated a high theoretical coverage of 99.95% across five African subregions, underscoring the advantage of region-specific vaccine design. The final construct exhibited favorable physicochemical properties, including an instability index of 29.00 and a Grand Average of Hydropathy (GRAVY) score of -0.304, indicating stability and hydrophilicity. Structural validation showed 95.6% residues in favored regions of the Ramachandran plot, with an ERRAT score of 98.86 and a ProSA Z-score of -3.26. Molecular docking with toll-like receptor 4 (TLR4) revealed strong binding interactions, including 35 hydrogen bonds and ten salt bridges. Immune simulation predicted robust humoral and cellular responses with memory cell formation, while normal mode analysis supported structural stability and flexibility. Furthermore, the construct was successfully codon-optimized (codon adaptation index: 0.97; GC content: 51%) and in silico cloned into the pET-28a(+) vector, indicating potential for expression in Escherichia coli. These findings support the theoretical feasibility of a population-specific rabies vaccine candidate and warrant further experimental validation.